2018
DOI: 10.18087/cardio.2018.12.10191
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of Cardioverter-Defibrillator in Children With Long-QT Syndrome: Assessment of Indications, Efficacy, and Safety Based on 10-Year Experience

Abstract: Purpose: to assess specificities of course of the long­QT syndrome in children before and after implantation of cardioverter­defibrillator (ICD), and optimization of indications to ICD­therapy.Materials and methods. We included in this study 48 children with long­QT syndrome from 44 unrelated families (28 boys and 20 girls), who underwent ICD implantation at the mean age 11.8±3.8 years. Mean duration of follow­up after implantation was 5.2±2.8 years. Data from these children were compared with those from 59 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Because of the occasional malign arrhythmias, medical therapies (beta blockers and other antiarrhythmics) and implantable cardiac defibrillators (ICDs) are the most commonly used treatment modalities. 3,4 Sinus bradycardia accompanying congenital LQTS is a known condition. 5 It is suggested that various types of LQTS gene mutations are also expressed in the human sinoatrial node (SAN), but the current data on the main mechanisms of SAN dysfunction due to LQTS is limited.…”
mentioning
confidence: 99%
“…Because of the occasional malign arrhythmias, medical therapies (beta blockers and other antiarrhythmics) and implantable cardiac defibrillators (ICDs) are the most commonly used treatment modalities. 3,4 Sinus bradycardia accompanying congenital LQTS is a known condition. 5 It is suggested that various types of LQTS gene mutations are also expressed in the human sinoatrial node (SAN), but the current data on the main mechanisms of SAN dysfunction due to LQTS is limited.…”
mentioning
confidence: 99%